2012
DOI: 10.1099/jmm.0.049635-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of drug-resistant Vibrio cholerae O1 causing endemic cholera in Dhaka, 2006–2011

Abstract: Vibrio cholerae O1 biotype El Tor (ET), causing the seventh cholera pandemic, was recently replaced in Bangladesh by an altered ET possessing ctxB of the Classical (CL) biotype, which caused the first six cholera pandemics. In the present study, V. cholerae O1 strains associated with endemic cholera in Dhaka between 2006 and 2011 were analysed for major phenotypic and genetic characteristics. Of 54 representative V. cholerae isolates tested, all were phenotypically ET and showed uniform resistance to trimethop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…The ctxB sequencing data (GenBank accession nos KT278766-KT278777) of the respective genotype, ctxB1 or ctxB7, were found to be consistent with the MAMA and DMAMA-PCR results. The ctxB genotyping data revealed that all V. cholerae O1 strains isolated from cholera cases had ctxB7 in 2010 (100 %; 11/11) and 2011 (100 %; 9/ 9), as reported earlier (Rashed et al, 2012). Although the number of V. cholerae clinical strains included in 2012 was low (n510), the majority of these strains (60 %; 6/10) carried ctxB1, and the ctxB7 was detected from the remaining V. cholerae associated with endemic cholera in Dhaka, Bangladesh.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…The ctxB sequencing data (GenBank accession nos KT278766-KT278777) of the respective genotype, ctxB1 or ctxB7, were found to be consistent with the MAMA and DMAMA-PCR results. The ctxB genotyping data revealed that all V. cholerae O1 strains isolated from cholera cases had ctxB7 in 2010 (100 %; 11/11) and 2011 (100 %; 9/ 9), as reported earlier (Rashed et al, 2012). Although the number of V. cholerae clinical strains included in 2012 was low (n510), the majority of these strains (60 %; 6/10) carried ctxB1, and the ctxB7 was detected from the remaining V. cholerae associated with endemic cholera in Dhaka, Bangladesh.…”
mentioning
confidence: 61%
“…cholerae was isolated from the stools of cholera patients admitted at the icddr,b Dhaka Hospital (Dhaka, Bangladesh); and the environmental isolates were from water samples routinely collected every fortnight from the water bodies in and around Dhaka city. A total of 151 conveniently chosen V. cholerae (70 clinical and 81 environmental) isolated between 2010 and 2014 by standard culture methods were subjected to phenotypic and genotypic tests (Alam et al, 2006;Rashed et al, 2012). All isolates were serologically confirmed to be V. cholerae O1, and possessed 'O' serogoup-specific gene wbe O1, further confirming the serological results; and they were positive for cholera toxin gene, ctxA (Hoshino et al, 1998).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…It was noted that altered El Tor strains replaced the prototype of the seventh pandemic El Tor in Asia (Evins et al, 1995;Nair et al, 2002) and Africa (Lizarraga-Partida et al, 2009;Morita et al, 2008). However, the Haitian ctxB variant of V. cholerae was reported to cause epidemics in Asia and Africa (Bhattacharya et al, 2016;Goel et al, 2008;Naha et al, 2012;Rashed et al, 2012;Talkington et al, 2011). Allelic variations in ctxB, tcpA and rstR are used as a marker to differentiate and characterize CTXF types and track the origin of strains.…”
Section: Discussionmentioning
confidence: 99%